AN OPTIMIZATION MODEL FOR CANE TRANSPORTATION IN THE ARGENTINE SUGAR INDUSTRY - Corsano, Gabriela; Melchiori, Luciana (Centro Azúcar Journal, 2025)
Introduction: Over the past decade, significant industrial and academic efforts focused on improving sugarcane harvesting, transportation, and sugar production have been carried out. While most studies focus on decision-making at a strategic and tactical level, the operational level remains less explored. This work develops a tool for daily sugarcane transportation planning within the Argentine industry. Objective: To generate a daily transportation schedule considering in-field loading and mill unloading activities, aiming to optimize transportation costs and synchronize truck arrivals. Materials and Methods: Sugarcane harvest scheduling involves cane cutting, loading in the field, transport, and mill unloading. These tasks greatly influence supply chain costs and production efficiency due to cane deterioration. To address this, we propose an Integer Linear Programming model that simultaneously assigns harvest fields, routes trucks, and schedules both loading and unloading operations. Results and Discussion: Two case studies assess the model: a small-scale instance for detailed result analysis and an industrial-scale example to demonstrate the model's scalability and effectiveness. Conclusions: The proposed model provides a comprehensive plan for sugarcane harvest and transport, supporting efficient operational decisions in the sugar industry.